ENSURING GENDER EQUALITY AS A KEY DIRECTION OF REFORMS IN NEW UZBEKISTAN - Seitova Z.P (Western European Studies, 2025)
In this article, the author examines issues of gender equality and how these issues are addressed at the state level. An analysis of sources that have covered equality issues in their publications is conducted. The article also explores how this issue currently stands at the state level.
Keywords: Uzbekistan; gender; laws; politics